2019
DOI: 10.1055/s-0040-1709685
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos comportamentais e ambientais associados às dificuldades alimentares na infância: Estudo com grupo controle

Abstract: Resumo Objetivos Investigar os fatores associados à presença de dificuldades alimentares (DAs) na infância, dentre dinâmicas de refeições e práticas parentais. Métodos Trata-se de um estudo observacional caso-controle. Para o grupo de crianças com queixas de DA, as informações foram retiradas dos prontuários dos pacientes. Para o grupo de crianças sem queixas de DA, a amostragem foi constituída por conveniência (abordagem de famílias nas unidades de pronto atendimento). As entrevistas foram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
(19 reference statements)
1
2
0
1
Order By: Relevance
“…In this research, the mealtime practice of children sharing the same family menu was inversely associated with FD, which was favorable to a child’s food acceptance, in accordance with the literature [ 16 , 59 ]. Similarly, Powell et al, [ 59 ] in a study with 2–4 years old American children, found less food refusal and easier feeding of children who did not use distractions and who had the practice of consuming the same meal as their mothers.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this research, the mealtime practice of children sharing the same family menu was inversely associated with FD, which was favorable to a child’s food acceptance, in accordance with the literature [ 16 , 59 ]. Similarly, Powell et al, [ 59 ] in a study with 2–4 years old American children, found less food refusal and easier feeding of children who did not use distractions and who had the practice of consuming the same meal as their mothers.…”
Section: Discussionsupporting
confidence: 90%
“…Given these findings, it is recommended that the options be guided within a limit of the preparations offered [ 63 ]. Still, a child’s autonomy and involvement in food choices should always be encouraged [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(14) Estudo realizado com o objetivo de identificar os fatores associados à presença de dificuldades alimentares na infância constatou, por meio de observação caso-controle, que 77% das crianças do grupo com dificuldades alimentares utilizam alguma distração durante as refeições, apresentando maior uso de distrações quando comparadas ao grupo controle (49,7%). (15) Sobre as dificuldades, algumas mães relataram a perda de apetite relacionado à erupção dos dentes decíduos como uma dificuldade para a alimentação da criança. Embora ainda não exista um consenso entre os especialistas sobre a associação de manifestações sistêmicas e locais com a erupção dentária, alguns estudos mostram que a perda de apetite é comumente relatada pelas mães durante essa fase.…”
Section: Discussionunclassified